Media freedom, polarization and democracy in post-communist Romania. Research notes - Grecu, Silviu-Petru; Chiriac, Horia-Costin (Technium Social Sciences Journal, 2024)
The paper aims to present the dynamics of the media freedom index in post-communist Romania. Using secondary statistical data regarding political, civic, and economic sectors, the paper indicates the complex interplay between democratic transition and media independence. As regards the “watchdog” and “agenda-setting” functions of mass media, the paper highlighted several statistical correlations that support the positive impact of participation and civil society in the field of media transparency and independence. The paper presents radiography of media freedom between 2002 and 2023, estimating the main variations of this index. Moreover, results confirm statistical differences between the two decades, highlighting that an increased level of media freedom was acquired after 2012. Political context, social dynamics, and economic conditions are several variables that are relevant for explaining the evolution of media freedom in Romanian society. Quantitative results show that political polarization is negatively related to media independence. Conversely, active citizens and civil society are key factors that could predict increased media freedom in Romanian post-communist society. The paper is useful for scholars and decision-makers interested in the complex interconnection between public information, media independence, and democratic consolidation.